COMPARATIVE CHARACTERISTICS OF TEACHING MATHEMATICS IN COLLEGES AND GYMNASIUMS IN GERMANY AND UKRAINE - Железнякова, Еліна; Сілічова, Тетяна (Професіоналізм педагога: теоретичні й методичні аспекти, 2020)
The article describes the main features, aspects and issues that can be problem for domestic applicants when they like to study at higher education institutions in Germany. The relevance of the issue under the study is proved by the fact that the global market of modern education is one of the most rapidly developing areas of the economy. In some countries, the profit from the export of educational services is so great, that it is one of the main sources of income for these countries. The number of students studying abroad is constantly growing. The main attention in the paper is paid to the fact that in addition to difficulties of psycho-social nature, a new style of life and new surrounding, the young people can encounter more serious difficulties: a mismatch in the level of professional training. The authors emphasize on the necessity to pay attention to the difference between the systems of school education in Ukraine and Germany. So they say that in Ukraine every student must have a complete school education to enter a higher education institution. If applicant graduates from a technical school (college), then he/ she has possibility to enter the second or the third year of studying at the corresponding University. In German the situation is different, its analysis is presented in the paper. There are noted not only main differences in education system as whole, but in the methods of teaching certain courses on example of teaching mathematics. The main focuses are made on the themes that are highlighted in the last school years, and themes of entrance exams at German universities. The analysis allows the authors to argue that preparing for further studying abroad is a complex process, requiring a difficult professional and educational training.